EDUKASI KEPADA PASIEN PENTINGNYA MEMBAWA KIB SEBAGAI UPAYA PERCEPATAN PELAYANAN KESEHATAN - Ernaman Putri, Riza Suci; Putri, Widya; Windharti, Ceriani (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2022)
To speed up the performance of registration officers in health services, education is carried out for patients regarding this medical identity card (KIB) so that patients realize the importance of bringing KIB when going for treatment. This community service activity was carried out at the Batam Botania Health Center, with the aim of providing counseling to patients about the importance of carrying KIB in order to speed up services and make services of a higher quality. The method used in this service is in the form of outreach, where the audience are patients who come to visit at the time of this counseling. Socialization is delivered through lectures with the help of audio-visual media, so that the material can be conveyed properly. The results of the activity show that socialization is going well and it is hoped that patients can receive material and raise awareness of the importance of carrying KIB during treatment.